The long-term outcomes of cirrhotic patients with pleural effusion - Hung, Tsung-Hsing (Saudi J Gastroenterol, 2018)
BACKGROUND/AIM: A pleural effusion is an abnormal collection of fluid in the pleural space and may cause related morbidity or mortality in cirrhotic patients. Currently, there are insufficient data to support the long-term prognosis for cirrhotic patients with pleural effusion. In this study, we investigated the short- and long-term effects of pleural effusion on mortality in cirrhotic patients and evaluated the benefit of liver transplantation in these patients. PATIENTS AND METHODS: The National Health Insurance Database, derived from the Taiwan National Health Insurance Program, was used to identify 3,487 cirrhotic patients with pleural effusion requiring drainage between January 1, 2007 and December 31, 2010. The proportional hazards Cox regression model was used to control for possible confounding factors. RESULTS: The 30-day, 90-day, 1-year, and 3-year mortalities were 20.1%, 40.2%, 59.1%, and 75.9%, respectively, in the cirrhotic patients with pleural effusion. After Cox proportional hazard regression analysis adjusted by patient gender, age, complications of cirrhosis and comorbid disorders, old age, esophageal variceal bleeding, hepatocellular carcinoma, hepatic encephalopathy, pneumonia, renal function impairment, and without liver transplantation conferred higher risks for 3-year mortality in the cirrhotic patients with pleura effusion. Liver transplantation is the most important factor to determine the 3-year mortalities (HR: 0.17, 95% CI 0.11- 0.26, P < 0.001). The 30-day, 30 to 90-day, 90-day to 1-year, and 1 to 3-year mortalities were 5.7%, 13.4%, 20.4%, and 21.7% respectively, in the liver transplantation group, and 20.5%, 41.0%, 61.2%, and 77.5%, respectively, in the non-liver transplantation group. CONCLUSION: In cirrhotic patients, the presence of pleural effusion predicts poor long-term outcomes. Liver transplantation could dramatically improve the survival and should be suggested as soon as possible.